2017
DOI: 10.25100/socolen.v43i2.5933
|View full text |Cite
|
Sign up to set email alerts
|

Modelización espacial de trips (Insecta: Thysanoptera) en el cultivo de aguacate (Persea americana)

Abstract: México es el principal productor y exportador de aguacate en el mundo. Los trips son considerados una de las principales plagas de este cultivo, ya que se alimentan del fruto pequeño y forman crestas o protuberancias, las cuales al crecer el fruto son más visibles, y este pierde valor económico. Además de este daño, las heridas causadas por los trips son el principal causante para que entre la enfermedad denominada roña de fruto. Las alternativas de control de los trips han carecido de eficacia debido, entre o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
1
Order By: Relevance
“…In the current study, the determination of the aggregated pattern in the spatial distribution model was completed using geostatistical methods. Compared with the estimation of the spatial distribution carried out with classical statistics, geostatistical methods provide a more direct measure of spatial dependence, because they consider the bidi-mensional nature of the organisms through their exact spatial location and it is independent of the relationship between mean and variance (Ramírez Dávila et al 2013; Rivera-Martínez et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, the determination of the aggregated pattern in the spatial distribution model was completed using geostatistical methods. Compared with the estimation of the spatial distribution carried out with classical statistics, geostatistical methods provide a more direct measure of spatial dependence, because they consider the bidi-mensional nature of the organisms through their exact spatial location and it is independent of the relationship between mean and variance (Ramírez Dávila et al 2013; Rivera-Martínez et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ramírez Dávila and Figueroa Figueroa (2013) used geostatistical tools to visualize its spatial distribution through maps by means of kriging with which it was observed that the insect does not invade 100% of the surface of the plot, allowing the identification of infested and infestation free areas. On the other hand, Rivera-Martínez et al (2017) indicate that the maps generated by sampling for the spatial modelling of thrips in avocado crop, allowed them to identify areas of infestation, finding that thrips population were distributed in 100% of the plot. Similar results were found by Paz and Arrieche (2017), who investigated geospatial distribution and population density of Thrips tabaci Lindeman (Thysanoptera: Thripidae) in onion production using geostatistics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insectos polífagos como los trips ocasionan raspaduras sobre el pericarpio del fruto que llevan a la formación de manchas de color café con aspecto corchoso y que también pueden favorecer el ingreso de otro tipo de patógenos al fruto. Su ataque en frutos pequeños también lleva a la generación de protuberancias venosas (Londoño, 2015;Rivera-Martínez et al, 2017). Los ácaros son otra plaga que viene afectando los cultivos de aguacate desde hace muchos años, producen manchas de color pardo-rojizo en el haz de las hojas y clorosis en el envés.…”
Section: Manejo De Plagas Y Enfermedadesunclassified